Laboratory Experiences for Prospective Science Teachers: A Meta-analytic Review of Issues and Concerns - Prabha, Shashi (European Scientific Journal, ESJ, 2016)
Prospective science teachers need to be prepared for making laboratory experiences integral part of teaching-learning of science in order to facilitate students to nurture their natural curiosity. This can engage students towards acquiring proficiency in the processes that can lead them to inquiry and generation and validation of scientific knowledge. This study is guided by the research question, “what is the status of laboratory experiences for prospective teachers?” and “what is missing in prospective science teachers’ preparation programme in order to bring excellence in science education?” An attempt has been made to carry out a meta-analytical review of the relevant literature to address some of the issues and concerns for providing laboratory experiences to prospective science teachers. Major issues emerging from the review of literature in this area are– recognizing need and understanding objectives of laboratory work from pedagogical prospective; integrating it with theory and providing laboratory experiences infused with inquiry.